2022
DOI: 10.1108/ijrdm-06-2021-0274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual stores' opaque exterior on store perceptions and purchase intentions

Abstract: PurposeA series of research has focused on how virtual reality (VR) technology itself influences consumers' perceptions and attitudes. However, little is known about consumers' unique perceptions and behaviours that can be generated by the specific factors of the virtual stores that they visit. Therefore, the authors examine how the specific aspects of the virtual stores that consumers see on screens – namely, the opacity of virtual stores' exterior design can impact consumer perceptions and behaviours.Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
(118 reference statements)
1
12
1
Order By: Relevance
“…Prior research on few occasions has shown that the effect of gender and age was not found to have moderating influence on consumers' participation intention and purchase behaviour (Betzing et al. , 2020; Han et al. , 2022).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Prior research on few occasions has shown that the effect of gender and age was not found to have moderating influence on consumers' participation intention and purchase behaviour (Betzing et al. , 2020; Han et al. , 2022).…”
Section: Discussionmentioning
confidence: 94%
“…TAM, TRA, UTAUT, U&G theory, telepresence theory) (Esmark Jones et al. , 2018; Han et al. , 2022; Shao and Lee, 2020) and different contexts (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2023), product virtualization technologies (Kim and Forsythe, 2007, 2010), telepresence or spatial presence (Smink et al. , 2020) and 3-D product presentation (Han et al. , 2022; Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…These tools enhance the shopping experience and arouse individual psychological state and encourage them to spend more time on shopping websites (Bonetti et al, 2018;Huang et al, 2017;Nagy and Hajdu, 2021). In apparel retailing, research suggests the relevance of technology like virtual-try-on (Patel et al, 2023), product virtualization technologies Forsythe, 2007, 2010), telepresence or spatial presence (Smink et al, 2020) and 3-D product presentation (Han et al, 2022;Yang et al, 2020a, b) in engaging online fashion consumers (Zou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%